(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: Approximately 20% of ischemic strokes affect the posterior circulation of brain structures. Mortality and risk of recurrent stroke are high with the possibility of misdiagnosis. As a result, an effective mode of examination is required for early diagnosis. Objective: To investigate the clinical diagnostic utility of brainstem auditory evoked potentials (BAEPs) in patients with posterior circulation ischemic stroke (PCIS). Methods: Twenty patients with PCIS aged 40 to 70 years were studied, along with 20 age-matched healthy controls. Medical history was taken, as well as a clinical neurological examination and BAEPs. Results: Waves IV and V latencies, and III-V inter-peak latencies were significantly prolonged and wave V amplitude was significantly reduced in patients with PCIS. Fifteen patients with PCIS show retrocochlear (central) dysfunction abnormality. Wave V latency and amplitude showed the highest estimated specificity and sensitivity with 80 % and 90%, respectively. Wave V latency negatively correlated with a duration from onset of stroke to neurophysiological examination. Conclusion: BAEPs are a useful tool as a biomarker for the clinical evaluation of PCIS. Wave V latency and amplitude is the most specific and sensitive among BAEPs parameter in the diagnosis of PCIS. Topographic distribution of the lost BAEP waves (according to diffusion-weighted MRI findings) may be closely linked to lost generators of individual waves, which suggests regional diagnostic validity of BAEPs. Finally, an early post-stroke BAEPs examination is better in detecting the abnormality and can provide reference values for further evaluation. Keywords: Posterior circulation ischemic stroke, brainstem auditory evoked potentials Citation: Tuaimeh MS, Hamdan FB, Al-Hamdani HA. Brainstem auditory evoked potential in patients with posterior circulation ischemic stroke. Iraqi JMS. 2022; 20(2): 191-200. doi: 10.22578/IJMS.20.2.5